Listening as productive skills: Reinventing classroom tasks - Dat Bao; Yongde Ye (Association for Scientific Computing Electrical and Engineering(ASCEE), 2022)
The article revisits the role played by listening skills in second language learning by challenging the perception of listening as a receptive skill. It argues that listening can be made productive by incorporating drama in classroom tasks to bring out more productive features of learning. To instantiate the implementation of drama, a listening activity is proposed with a framework. The article opens a new dialogue in scholarly characterisation of language skills through re-visualising what learners can perform during listening tasks as well as how this performance can stretch our conventional thinking about the nature of language practice.